2014
DOI: 10.5430/jha.v3n6p127
|View full text |Cite
|
Sign up to set email alerts
|

Physician experiences of patient-centered and team- based ward rounding – an interview based case-study

Abstract: Background: Rounding has long traditions within hospital-based healthcare, as a way to organize the ward-based part of the care and cure process. Despite an increased emphasis on patient participation, there has been limited research exploring physician experiences of actually applying these principles to the ward round.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The macro‐level institutional norms that guide clinical practice and micro‐level patterns of behaviour and cognition that shape the reality surrounding the physician–patient encounter have developed separately rather than interactively . As the fragmentation of hierarchal and relational governance persists, we advocate the integration of these dialectically related domains through the involvement of patients and community in health‐care decisions and priority setting . This article discusses the consumerist reasons of the current exclusion of patient voices from hierarchical governance initiatives and elaborates on the moral duty of patients–citizens to get involved in medical policymaking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The macro‐level institutional norms that guide clinical practice and micro‐level patterns of behaviour and cognition that shape the reality surrounding the physician–patient encounter have developed separately rather than interactively . As the fragmentation of hierarchal and relational governance persists, we advocate the integration of these dialectically related domains through the involvement of patients and community in health‐care decisions and priority setting . This article discusses the consumerist reasons of the current exclusion of patient voices from hierarchical governance initiatives and elaborates on the moral duty of patients–citizens to get involved in medical policymaking.…”
Section: Resultsmentioning
confidence: 99%
“…10 As the fragmentation of hierarchal and relational governance persists, 6 we advocate the integration of these dialectically related domains through the involvement of patients and community in health-care decisions and priority setting. 72 consumerist reasons of the current exclusion of patient voices from hierarchical governance initiatives and elaborates on the moral duty of patients-citizens to get involved in medical policymaking. Relying on the (strong) structuration theory which uncovers how macro-and micro-level devices shape each other's structure via mutually reinforcing cycles of influence, we argue that health-care organizations would benefit from the incorporation of interactional processes under institutional infrastructures which provide the foundation for these interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baathe et al50 have studied a similar model for rounds and have shown that a number of physicians felt that their autonomy was limited and that they were uncomfortable with running the risk that potential gaps in their knowledge would be revealed in front of the other participants in the round. In another study, it was observed that nurses could be unsure whether a physician appreciated it when nurses took the initiative, based on their knowledge, to develop patient-centered rounds 51.…”
Section: Discussionmentioning
confidence: 99%
“…This is something that could be particularly important with frail elderly people, but is also an offer that almost any patient might welcome if given the choice. There are already places where practices such as these are being adopted 5. Caldwell argues this should now be far more widespread.…”
Section: Solving the Problemsmentioning
confidence: 99%